2004
DOI: 10.1097/01.gim.0000118061.66602.a5
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in exon 14 of dihydropyrimidine dehydrogenase and 5-Fluorouracil toxicity in Portuguese colorectal cancer patients

Abstract: Purpose: Dihydropyrimidine dehydrogenase is a critical enzyme in the catabolism of 5-Fluorouracil, a drug frequently used in cancer therapy. Patients with deficient dihydropyrimidine dehydrogenase activity are at risk of developing severe 5-Fluorouracil-associated toxicity. Genetic analysis of the gene coding for dihydropyrimidine dehydrogenase has shown that mutations in exon 14, especially the splice-site mutation IVS14ϩ1G3 A, were associated with dihydropyrimidine dehydrogenase enzymatic deficiency. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 15 publications
1
23
1
Order By: Relevance
“…Previous observations confirmed the high specificity, positive and negative predictive values of this genetic analysis[6,14,30]. However, our previous analysis of 73 consecutive colorectal cancer patients detected exon 14 mutations in only two of eight cases with severe toxicity[29]. …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Previous observations confirmed the high specificity, positive and negative predictive values of this genetic analysis[6,14,30]. However, our previous analysis of 73 consecutive colorectal cancer patients detected exon 14 mutations in only two of eight cases with severe toxicity[29]. …”
Section: Discussionsupporting
confidence: 79%
“…All patients enrolled in this study were screened for DPYD exon 14 mutations by sequencing (including the exon 14 skipping mutation IVS14+1G > A), eight of which were included in a previous publication on unselected colorectal cancer patients[29]. This mutation was found in two patients (one previously reported) and both of them developed severe toxicity following 5-FU administration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a correlation between the DPYD*2A variant and reduced enzyme activity in peripheral blood mononuclear cells (PBMCs) was found in several ex vivo studies that confirmed decreased function of DPYD*2A [26,[28][29][30] and consequently an association was also found between DPYD*2A and reduction in fluoropyrimidine clearance in patients [31,32]. In numerous studies an association between DPYD*2A allele carriership and the increased risk of toxicity related to fluoropyrimidine treatment was confirmed [4,24,31,[33][34][35][36][37][38][39][40][41][42][43][44][45]. For example, in a meta-analysis by Terrazzino et al a strong correlation between the DPYD*2A allele and overall grade ≥3 toxicity was found (odds ratio 5.42, p < 0.001) [33].…”
Section: Previous Guidelines and Recommendationsmentioning
confidence: 82%
“…Simultaneously, our work was [4,8,10,11,19,27,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] DPYD*13 (rs55886062) [4,19,30,32,33,46,49,50] 0.5 c.2846A>T (rs67376798) [4,13,24,33,36,41,42,44,47] c.1236G>A/ HapB3 (rs56038477) [14,15,42,44,46,47,49,50,56] 1 DPYD*1 (wild-type)…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of low DPD enzymatic activity, indicating partial DPD deficiency, in the general population was initially estimated at between 3% and 5% [62]. Additional studies have shown significant variability among different ethnic subpopulations, showing that the prevalence of partial DPD deficiency is higher in Asian [63], Southwest Asian [64], African [65], American [66] than European and Caucasian Group [67,68].…”
Section: Dihydropyrimidine Dehydrogenase (Dpd)mentioning
confidence: 99%